(untitled) (PUBMET, 2022)
European Open Science Cloud (EOSC) is an European wide initiative that aims to develop a ‘Web of FAIR Data and Services’ for science in Europe that will provide researchers, students, companies and citizens with a federated and open multi-disciplinary environment where they can collaborate, share and reuse data, tools and services. EOSC Portal Catalogue and Marketplace is an entry point which improves the findability and accessibility of the scientific resources, their curation, support and training activities. In order to empower local stakeholders (researchers, policy makers, research performing organisations, etc.), NI4OS-Europe project (National Initiatives for Open Science in Europe) provides technical support for onboarding, i.e. making scientific web services compliant with the NI4OS/EOSC requirements and inclusion in catalogues. At the same time, as open science cloud initiatives emerge across the EU landscape, in the terms of infrastructure and policy development, it also supports building the Croatian Open Science Cloud (abbrev. locally HR-OOZ) Initiative. HR-OOZ is gathering prominent national institutions with an active role regarding open science covering all important stakeholder groups: research performing organisations (RPO), research funding organisations, research supporting organisations and policy makers. The Initiative aims to build a modern, high-quality, internationally relevant, and competitive science system based on the principles of open science, which is harmonised and connected with the European Research Area and relevant European initiatives. The Initiative has two main goals. The first goal is to set up the HR-OOZ which includes tasks of defining its organisational structure, defining the technological principles of services that will make the HR-OOZ, and ensuring its sustainability. The second goal of the Initiative is to draft the proposal of the National Action Plan for Open Science and propose changes to the law governing scientific activities. We will present the interconnections between national and European initiatives and how they complement each other as well as the proposed mechanisms for incentivizing and rewarding OS practices which are the vital components of the whole OS ecosystem.